Differences in total phenolics, antioxidant activity and metabolic characteristics in peach fruits at different stages of ripening. (15th March 2023) - Li, Yong; Li, Lu; Zhang, Xiping; Mu, Qi'er; Tian, Ju; Yan, Juan; Guo, Lei; Wang, Ya; Song, Lixiao; Yu, Xiangyang
Abstract: Fruit ripening is a complex process in the final phase of fruit development, which determines the quality and nutrient composition of fleshy fruits. In the present study, the total phenolics, antioxidant activity and metabolic characteristics of peach fruits named " Jinlinghuanglu " during ripening were investigated. Four ripening stages were considered including unripe, semi-ripe, fully ripe and overripe. Our result showed that both the total phenolics and antioxidant activity decreased gradually with peach ripening. Metabolomics demonstrated that most synthesis-related amino acids and polyphenols were significantly decreased in the semi-ripe stage, compared to the unripe stage, whereas four flavonoids relevant to coloring were significantly increased. Many amino acids, sugars and organic acids were accumulated at the fully ripe stage, which may give peach good flavour and taste. At the overripe stage, most amino acids, sugars and polyphenols were preferentially consumed due to climacteric respiration. However, some phospholipids, nucleosides and mucic acid (linked to cell wall metabolism) were significantly accumulated due to cell hydrolysis, which could be used for judging the best picking period. Our data not only revealed the change in the nutrition composition of peach fruits during ripening, but also demonstrated the value of metabolomics in characterizing the mechanism of fruit quality development. Highlights: Peach fruits at unripe, semi-ripe, fully ripe and overripe stages were analysed. Many amino acids, sugars and organic acids were accumulated at fully ripe stages. Lipids, nucleosides and mucic acid were increased due to cell hydrolysis at overripe. Most phenolic acids and flavonoids were gradually decreased with peach ripening. Biomarkers relevant to the process of peach ripening and coloring were found.